Peran Guru Profesional Pendidikan Agama Islam dalam Pembinaan Akhlakul Karimah Siswa di SMA Negeri 1 Polokarto Sukoharjo Tahun Pelajaran 2022/2023 - Aisyiah Fitri Aulia; Nur Hidayah; Sugiyat Sugiyat (Journal on Education, 2023)
This study aims to find out the role of professional Islamic Religious Education teachers in fostering students' akhlakul karimah, and what are the supporting and inhibiting factors in fostering good behavior students at SMA Negeri 1 Polokarto. The role of the teacher is an action taken by the teacher to achieve educational goals. Good behavior fostering students is a process or effort in perfecting noble behavior or character so that they become individuals who reflect good behavior. Researcher used qualitative research methods with a descriptive approach. Researcher used the method of observation, interviews, and documentation in collecting data. Data analysis in this study used three stages of analysis, including data reduction, data presentation, and drawing conclusions. Checking the validity of this research data uses a credibility test, transferability test, dependability test, and confirmability test. The results of this study are: the role of professional Islamic Religious Education teachers in fostering students' akhlakul karimah at SMA Negeri 1 Polokarto shows that Islamic Religious Education teachers play an active role as educators, mentors, facilitators, communicators, and motivators in fostering students' akhlakul karimah. Supporting factors in the development of akhlakul karimah include 1) school environment, 2) school facilities and programs, 3) cooperation between teachers. The factors that hinder the development of akhlakul karimah in students include 1) student background, 2) friends, 3) students who are difficult to advise.